Toward a functional neuroanatomy of semantic aphasia: A history and ten new cases. (December 2017) - Dragoy, Olga; Akinina, Yulia; Dronkers, Nina
Abstract: Almost 70 years ago, Alexander Luria incorporated semantic aphasia among his aphasia classifications by demonstrating that deficits in linking the logical relationships of words in a sentence could co-occur with non-linguistic disorders of calculation, spatial gnosis and praxis deficits. In line with his comprehensive approach to the assessment of language and other cognitive functions, he argued that deficits in understanding semantically reversible sentences and prepositional phrases, for example, were in line with a single neuropsychological factor of impaired spatial analysis and synthesis, since understanding such grammatical relationships would also draw on their spatial relationships. Critically, Luria demonstrated the neural underpinnings of this syndrome with the critical implication of the cortex of the left temporal-parietal-occipital (TPO) junction. In this study, we report neuropsychological and lesion profiles of 10 new cases of semantic aphasia. Modern neuroimaging techniques provide support for the relevance of the left TPO area for semantic aphasia, but also extend Luria's neuroanatomical model by taking into account white matter pathways. Our findings suggest that tracts with parietal connectivity – the arcuate fasciculus (long and posterior segments), the inferior fronto-occipital fasciculus, the inferior longitudinal fasciculus, the superior longitudinal fasciculus II and III, and the corpus callosum – are implicated in the linguistic and non-linguistic deficits of patients with semantic aphasia.